A petrographical and mineralogical investigation of the rocks of the Bushveld Igneous Complex in the Tauteshoogte-Roossenekal area of the Eastern Transvaal - upetd@up.ac.za (University of Pretoria, 2013)
Thesis (DSc)--University of Pretoria, 2012.